A vectorial DEVS extension for large scale system modeling and parallel simulation. (May 2014) - Bergero, Federico; Kofman, Ernesto
In this article we introduce an extension to the Discrete Event System (DEVS) formalism called Vectorial DEVS (VECDEVS) that allows to represent large scale systems in a graphic block diagram way. A pure VECDEVS model basically consist in an array of identical classic DEVS models that may differ in their parameters. The interconnection of VECDEVS models with some special classic DEVS models that can handle VECDEVS events allows us to easily represent large systems of arbitrary structure. A noticeable feature of this extension is that VECDEVS models can be easily split for parallel simulation. For that purpose, we developed an algorithm that automatically splits VECDEVS models into an arbitrary number of sub-models for parallel simulation. The implementation of VECDEVS and the partitioning algorithm in a DEVS simulation tool is also described and its usage is illustrated through some application examples.